Characterising the role of climate change in perpetuating Zimbabwean farmers' health risks from exposure to endocrine disrupting pesticides - Zinyemba, Cliff (Department of Public Health and Family Medicine, 2020)
Climate change and endocrine disrupting chemicals are currently amongst key drivers for a range of non-communicable diseases and adverse human health conditions. Pesticides constitute an important source of endocrine disrupting chemicals. A growing public health concern is the potential relationship between climate change and adaptive increases in agricultural pesticide use. Effectively, with increases in pesticide use, there may be increased potential for elevated pesticide exposures and, thus, increased endocrine disrupting health risks. The aim of this thesis was to assess whether climate change is a key risk perpetuating factor for endocrine disrupting health risks due to increased agricultural pesticide uses and exposures. The study was conducted in Zimbabwe with farmers in the cotton farming district of Rushinga. Three research methods: 1) interviews with farmers, 2) quantitative structure-activity relationship modelling and, 3) stakeholder interviews with government cotton agronomists working in Rushinga district who acted as key informants. Qualitative in-depth interviews were conducted with 50 active smallholder farmers who had grown cotton for a minimum of 30 years. The interviews gathered farmers' perceptions and observations regarding climate change, changes in pest types, pest populations, pesticide use patterns, pesticide handling practices, and adaptive practices, amongst others. Quantitative structure-activity relationship modelling was, further, applied in identifying key risk pesticides of concern. Amitraz, endosulfan, fenvalerate and lambda-cyhalothrin were determined as having a high likelihood of acting as endocrine disruptors, as validated by literature highlighting the four pesticides' hormone-related cognitive, physiological and reproductive adverse health effects. Findings indicated that a number of farmers' adaptative practices were found to be incremental and, potentially, maladaptive, thereby enhancing pesticide use and exposure. This was indicative of climate change's potential for perpetuating pesticide-related endocrine disrupting health risks. Opportunities exist, however, for farmers to reduce pesticide use, and, thus, potential endocrine disrupting health risks through certain autonomous transformational adaptive practices, such as crop switching and cotton acreage reduction. Assistance to farmers by the government and development agencies, for enhancing opportunities for transformational adaptation is therefore recommended. Furthermore, there is need, at policy level, for phasing out pesticides with endocrine disrupting properties. There is, furthermore, a clear need for enhancing farmers' access to, and comprehension of, pesticide risk information through various innovative means, including research translation to reduce exposure risks.